Dark matter in flavour physics - Šadl, Mitja (Matrika, 2018)
This article presents dark matter from the particle physics point of view. Initially, we present an overview of the Standard Model. Then we explain, why there is dark matter in our Universe and what could be its constituents. What follows, is the description of dark sectors, proposed by particle physics as a source of dark matter candidates. Next, we discuss two models, one dealing with axions and the other with dark gauge bosons or dark photons. We focus more on the latter one. In conclusion, we look at the opportunities for future experiments.
Keywords: cosmology; dark matter; fizika delcev; kozmologija; particle physics; Standard Model; standardni model; temna snov